Experimental Methods for the Study of Rocks Dislocation within the Energy Mining Industry from Romania - Sorina D. Stanila; Adriana Zamora; Daniel N. Fita; Mila Ilieva Obretenova (Science and Technology - Recent Updates and Future Prospects Vol. 4, 2024)
The present study highlights experimental methods for the study of rock dislocation within the energy mining industry in Romania. Dislocations in rocks with knives have a long history, but the share of coal mining in the worldwide energy mining industry, as well as the nature and physical-mechanical properties of coal, favored and determined the continuous development of mechanization systems specific to their extraction process. The introduction of mining combines, which stand for highly complex infrastructures capable of guaranteeing the extraction process’s full mechanization and uninterrupted flow, marked a turning point in the history of coal mining mechanization. Mining combines are extremely productive devices that enable the simultaneous processing of material displacement from the working front to crushing, grinding, and loading. The main advantages that characterize them over other means of exploitation are: rhythmic development of the work process in the abattage; improvement of the conditions for directing the mining pressure; increase of the speed of advancement of the front, increase of production and labor productivity; improving working conditions and safety during work. The authors analyze the following essential aspects: parameters of cutting rocks using knives, constructive aspects related to knives of mining combines, types of methods of dislocation of rocks, etc, in order to identify possible ways to improve the performance of mining combined knives, and this is done.